Some techniques of equirhythmic translation (based on Russian covers of foreign songs) - G.S. Mkhitaryan (Ученые записки Казанского университета: Серия Гуманитарные науки)
Translation techniques used to adapt original song lyrics to other languages were considered. The research is highly relevant, because no methodological basis has been developed for equirhythmics as a special type of translation. A total of 272 cases obtained by the method of continuous sampling among the Russian covers of foreign songs were analyzed. A variety of lexical, grammatical, and lexical-grammatical equirhythmic translation techniques were singled out: generalization, omission, expansion, integral transformation, change of grammatical indicators, etc. The important influence exercised by the equiphonic component on the quality of equirhythmic translation was emphasized. It was concluded that equirhythmic translation is extremely challenging, but it provides a whole number of opportunities for translators to create a highly equivalent and adequate covers of foreign songs.